University Students’ Perception of MOOCs based on MOOC Instructional Design Elements - Zainab Shahzadi Javed, Zohra Nazeer, Muhammad Umair (PJDOL, 2023)
his study aimed to investigate university students' overall perception of MOOCs based on the instructional design elements of MOOCs. Due to the increase in enrollment in MOOCs, it is essential to understand students' general perception of them. Additionally, only a few studies have been conducted on MOOCs in developing countries.